Validation of the scale for assessing depression and its relation to technology dependence - Guimarães,Flávia Leite (2019)
ABSTRACT BACKGROUND: The daily coexistence with the technologies (computer, mobile phone, tablet, among others), begins to produce significant changes in human behavior. We have observed that there is an association between dependence on technologies and major depressive disorder, as well as with other mental disorders. OBJECTIVE: To validate a scale for assessing depression and its relation to dependence on everyday technologies. METHODS: Validation of a Technology Dependent Depression Scale (TDDS) was performed in 5 phases: (1) initial scale construction with 20 questions; (2) expert evaluation; (3) application to 100 volunteers, (4) statistical analysis and results, (5) preparation of the final version of the validated TDDS. RESULTS: We used the R statistical program, version 3.4.2 and the “dplyr” package to present descriptive statistics, hypotheses tests of mean differences and factorial analysis. The results provided a validated and approved final version for TDDS. CONCLUSIONS: We constructed the final version of the validated TDDS, which is adequate for clinical contexts and to be used in future research. All the psychometric properties were checked for accuracy, reliability, presentation, clarity, pertinence and comprehension of the instrument conferring validity to the end-product.